Perlindungan Hukum Bagi Karyawan Terhadap Pelanggaran Kontrak Kerja Perusahaan (Studi Kasus Sport Station) - Putri, Tasya Aryfka; Hasanah, Uswatun; Marlinah, Marlinah (RIO LAW JURNAL, 2025)
This research aims to identify the forms of employment contract violations that occur at Sport Station and to analyze the effectiveness of legal protection available to employees, especially those bound by Fixed-Term Employment Agreements (PKWT). The research method used is empirical legal research with a socio-legal approach, combining document analysis with in-depth interviews involving employees, company representatives, and the Manpower Office of Bengkulu City. The study found various violations of PKWT provisions, including the absence of contract copies, verbal contract extensions, unilateral termination of employment, and neglect of normative employee rights such as social security and leave. Although legal protection is normatively available through labor regulations and industrial dispute resolution mechanisms, its effectiveness remains limited due to structural barriers, low legal literacy among workers, and unequal bargaining power between employees and employers. These findings reinforce legal protection theory, justice theory, and critical legal theory, all of which highlight the imbalance of power in the world of work. This study recommends strengthening labor law enforcement, providing effective internal grievance mechanisms, and increasing legal education for workers. Keywords: Legal protection, employment contract, PKWT, labor law.